Initial experience with transmural use of a new endoscopic ultrasound electric core needle biopsy device: Case series - Mendoza Ladd, Antonio; Alsamman, Amer; Meiklejohn, Karleen; Viramontes, Omar (Endoscopy International Open, 2024)
Background and study aims Endoscopic ultrasound-guided biopsy via fine-needle biopsy/fine-needle aspiration (FNB/FNA) is currently the standard method to sample tumors in the mediastinum and abdomen. Although specimens obtained with these needles are acceptable, a histological diagnosis is not always possible. Recently, a new EUS-guided core needle biopsy (EUS-CNB) device became available. Herein, we describe the first experience with its use in a transmural fashion.Patients and methods This was a case series of patients who underwent EUS-CNB at an academic center. All patients provided written informed consent and were observed in the hospital ≥ 48 hours after the procedure.Results A total of 8 patients underwent EUSC-CNB: five in the pancreas, two in the retroperitoneum, and one in the mediastinum. The diagnostic accuracy of EUS-CNB was 100% after one actuation. In four patients, same-session FNB and EUS-CNB were obtained from the same lesion with superior tissue sample in the latter. No adverse events were documented.Conclusions To our knowledge this is the first report on transmural use of EUS-CNB in gastroenterology. Our findings suggest that the device is effective and safe. Larger studies comparing it with FNA/FNB needles will be required to further assess performance and safety.
Keywords: Endoscopic ultrasonography; Pancreas; Tissue diagnosis; Fine-needle aspiration/biopsy; Endoscopy Upper GI Tract; Precancerous conditions & cancerous lesions (displasia and cancer) stomach